Reform of the global financial architecture - Garry J. Schinasi; Edwin M. Truman (Bruegel, 2010)
This paper examines the implications of the global financial crisis of 2007-10 for reform of the global financial architecture, in particular the International Monetary Fund and the Financial Stability Board and their interaction. These two institutions are not fully comparable, but they must work more closely in the future to help prevent global financial crises. To this end, the paper identifies institutional and substantive reforms separately and in their joint work that would be desirable and appropriate.
Keywords: F30; F33; F36; F53; G28; 330; International Monetary Fund; Financial Stability Board; Bank for International Settlements; Group of Twenty; banking supervision and regulation; financial crises; financial stability; financial reform; Internationales Finanzsystem; Finanzkrise; Internationale Wirtschaftsorganisation; Finanzsektor; Reform; Bankenregulierung; Welt